Curtains Up! Shifting Emotional Styles in Gay Men’s Venues Since the 1950s - Gammerl, Benno (SQS – Suomen Queer-tutkimuksen Seuran lehti, 2017)
This opinion piece enquires into the history of male homosexuality in West Germany since the 1950s and focuses on the transition from the homophile bar to the gay disco as a prototypical meeting place for same-sex desiring men. Which emotional shifts did this spatial variation entail? Based on oral history interviews and gay magazines, the analysis explores intricate changes in queer everyday life beyond the all too simple supposition that closeted shame was supplanted by openly gay pride. In addition, the study shows on a methodological level that the allegedly antagonistic approaches in emotion research – constructionism, praxeology, affect-theory and phenomenology – can actually be fruitfully combined with each other, especially when it comes to analysing the interplay between spaces and feelings.